Cross?correlation wavelet?domain?based particle swarm optimization for lightning mapping - Alammari A.; Alkahtani A.A.; Ahmad M.R.; Aljanad A.; Noman F.; Kawasaki Z. (MDPI, 2023)
Several processing methods have been proposed for estimating the real pattern of the temporal location and spatial map of the lightning strikes. However, due to the complexity of lightning signals, providing accurate lightning maps estimation remains a challenging task. This paper presents a cross?correlation wavelet?domain?based particle swarm optimization (CCWD?PSO) technique for an accurate and robust representation of lightning mapping. The CCWD method provides an initial estimate of the lightning map, while the PSO attempts to optimize the trajectory of the lightning map by finding the optimal sliding window of the cross?correlation. The technique was further enhanced through the introduction of a novel lightning event extraction method that enables faster processing of the lightning mapping. The CCWD?PSO method was validated and verified using three narrow bipolar events (NBEs) flashes. The observed results demonstrate that this technique offers high accuracy in representing the real lightning mapping with low estimation errors. 2021 by the authors. Licensee MDPI, Basel, Switzerland.